'Daddy, I'm falling for a monster': Women, Sex, and Sacrifice in Contemporary Paranormal Romance. Issue 1 (May 2019) - Chaplin, Sue
Abstract : This paper examines a key trope within much contemporary paranormal romance: the absence, or ineffectiveness, of the father. The first part of the essay develops an analysis of this aspect of the genre (in the Twilight Saga especially) through the work of René Girard, Luce Irigaray, and Juliet MacCannell. Of particular importance here is the extent to which Twilight and similar narratives stage female self-sacrifice as a pre-condition for the redemption of the hero and the restoration of patriarchal bonds initially compromised by some crisis in the effective functioning of paternal authority. The second section extends this analysis to consider ways in which paranormal romances featuring werewolves and vampires shift away from this conservative and reductivist romance paradigm so as to affirm and contest heteronormative, paternalistic models of masculinity and sexual desire.